P3.431 Impact of Social Marketing to Promote Awareness of "Early" HIV Testing in Addition to Pooled Nucleic Acid Amplification Testing in Men Who Have Sex with Men in Vancouver, British Columbia. (13th July 2013) - Gilbert, M; Cook, D; Steinberg, M; Kwag, M; Robert, W; Doupe, G; Krajden, M; Rekart, M
Abstract : Background: The contribution of acute HIV infection (AHI) to transmission is widely recognised. Increasing AHI diagnosis capacity can enhance HIV prevention through subsequent behaviour change or intervention. We examined the impact of targeted pooled NAAT and social marketing to increase AHI diagnosis among men who have sex with men (MSM) in Vancouver, British Columbia. Methods: We implemented pooled NAAT following negative 3 rd generation EIA testing for males ≥ 19 years in six clinics accessed by MSM, accompanied by two social marketing campaigns developed in partnership with a community-based gay men's health organisation (campaigns emphasised availability of "early" testing for AHI and promoted early testing following potential exposure or new relationship). We compared test volume and diagnosis rates for pre- (April 2006-March 2009) and post-pooling (April 2009-March 2012) periods, and calculated diagnostic rate and yield, RNA copy number, time to results and cost per diagnosis. Results: Post-pooling, the AHI diagnosis rate increased from 1.0 to 1.84 per 1, 000 tests; quarterly AHI diagnosis rates increased significantly. Of 217 new HIV diagnoses post-pooling, 54 (24.9%) were AHI (25 detected by pooled NAAT only) for an increased diagnostic yield of 11.5%. AHI detected by pooled NAAT had higher median RNA copies (7.77 × 10 5 copies/mL) and similar time to result (median 7 days) compared to AHI detected through 3rd generation EIA (4.96 × 10 5 copies/mL; median 6 days). The incremental cost per AHI diagnosis through pooled NAAT was 9, 124 CDN. Conclusions: Few studies have assessed the contribution of social marketing in enhancing capacity for AHI diagnosis. Our study suggests that targeted implementation of pooled NAAT at clinics accessed by MSM accompanied by local social marketing campaigns is effective at increasing AHI diagnoses, and is likely cost-saving.